Oil-Type Sunflowers Cost-Return Budget (W-SF-F Rotation) in Western Kansas - O'Brien, Daniel M.; Sartwelle III, James D. (My University, 1997)
This publication projects a budget that reflects expected income and costs based on typical production practices of sunflowers in western Kansas.
MF887_1997_10
Keywords: MF887; Economics; Crops; MF